(untitled) (Journal of Natural Language and Linguistics, 2024)
Today, many students face with the English speaking difficulties during conversations, because of these problems most of EFL (English as Foreign Language) students deny to speak in English and have a preference to use their mother language. So, the research tried to do a study based on the “The difficulties of EFL students in speaking English at Sar-e-Pul Higher Education Institute.” This research aims to find out the difficulties, and factors caused problems while students speaking English. This research was conducted at Sar-e-Pul Higher Education Institute. It helps the students to know the factors which caused problems in speaking. The participants were 20 male students from third class of English language and literature department of Sar-e-Higher Education Institute. The data was collected through a questionnaire that is consisted of 12 questions. An instrument consisting of twelve questions was used to gather the data. The SPSS application was used to examine the gathered data. The majority of pupils, the study discovered, struggle with a variety of aspects of speaking English, including vocabulary, pronunciation, grammar, and confidence issues.